Meningkatkan Hasil Belajar Siswa Pada Tema “Indahnya Keberagaman Di Negeriku” Melalui Pendekatan Kontekstual Di Kelas IV: Improving Student Learning Outcomes on the Theme of “The Beauty of Diversity in My Country” Through a Contextual Approach in Grade IV - Faizal Faizal; Muhammad Aqil; Nurul Fitriah Aras; Surahman Surahman (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
through two cycles, each cycle consisting of four stages (a). Planning (b). Implementation of Action (c). Observation and (d). Reflection. The study has an important objective in improving student learning outcomes on the theme "The Beauty of Diversity in My Country" in Class IV SDN 18 Banawa. The problem to be studied is the low learning outcomes of students. In an effort to solve this problem, the researcher used a contextual approach. The subjects to be studied were 29 students of class IV SDN 18 Banawa. The results of the data obtained through teacher and student activity sheets and action result tests. Data from the results of the first cycle of research showed the results of students' Classical Absorption Power of 57.93% and the percentage of Classical Learning Completeness of 52.63%. While in cycle II, the percentage of Classical Absorption Power was 87.24% and the percentage of Classical Learning Completeness of 96.55%. Based on the results of the percentage of Learning Outcome Completeness in Cycle I and Cycle II. It is clear that the increase that occurred was very significant, namely 30.81% for Individual Absorption Power, from cycle I of 58.24% and cycle II of 89.05%. The same is true for Classical Learning Completeness which experienced a very large increase, namely 62.16% from cycle I of 56.63% and cycle II of 96.55%. Based on these results, researchers can conclude that using a contextual approach can improve student learning outcomes.